Comparative Transcriptome Analysis Between Resistant and Susceptible Rice Cultivars Responding to Striped Stem Borer (SSB), Chilo suppressalis (Walker) Infestation - Wang, Yue; Ju, Di; Yang, Xueqing; Ma, Dianrong; Wang, Xiaoqi (Frontiers in Physiology, 2018)
The striped stem borer, Chilo suppressalis (Walker), is a notorious pest of rice that causes large losses in China. Breeding and screening of resistance rice cultivars are effective strategies for C. suppressalis management. In this study, insect-resistant traits of 47 rice cultivars were investigated by C. suppressalis artificial infestation (AI) both in field and greenhouse experiments, using the susceptible (S) cultivar 1665 as a control. Results suggest that two rice cultivars, namely 1688 and 1654, are resistant (R) and moderately resistant (MR) to C. suppressalis, respectively. Then, a comparative transcriptome (RNA-Seq) was de novo assembled and differentially expressed genes (DEGs) with altered expression levels were investigated among cultivars 1688, 1654 and 1665, with or without C. suppressalis infestation for 24h. A total of 2569 and 1861 genes were up-regulated, and 3852 and 1861 genes were down-regulated in cultivars 1688 and 1654, respectively after artificial infestation with C. suppressalis compared to the non-infested control (CK). For the susceptible cultivar 1665, a total of 882 genes were up-regulated and 3863 genes were down-regulated after artificial infestation with C. suppressalis compared to the CK. Twenty four DEGs belong to proteinase inhibitor, lectin and chitinase gene families; plant hormone signal transduction and plant-pathogen interaction pathways were selected as candidate genes to test their possible role in C.suppressalis resistance. RT-qPCR results revealed that 13 genes were significantly up-regulated and 8 were significantly down-regulated in the resistant cultivar 1688 with C. suppressalis artificial infestation (1688AI) compared to the CK. Three genes, LTPL164, LTPL151, and LOC Os11g32100, showed more than a 10-fold higher expression in 1688AI than in 1688CK, suggesting their potential role in insect resistance. Overall, our results provide an important foundation for further understanding the insect resistance mechanisms of selected resistant varieties that will help us to breed C. suppressalis resistant rice varieties.